1994
DOI: 10.1002/art.1780370614
|View full text |Cite
|
Sign up to set email alerts
|

Preferential utilization of a novel vλ3 gene in monoclonal rheumatoid factors derived from the synovial cells of rheumatoid arthritis patients

Abstract: Objective. To further our understanding about the molecular genetics of rheumatoid factor (RF) in rheumatoid arthritis (RA).Methods. The heavy and light chain variable region (V) genes of 5 new human monoclonal IgM RFs were cloned and sequenced using the polymerase chain reaction and the dideoxynucleotide termination method.Results. The results reveal the recurrent usage in two RA patients of a novel VA3 germline gene, designated Humlv3c93. Specifically, in 2 of 3 RFs (C93 and D53) from one patient, the light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Recently, it has been confirmed that the corresponding germline gene 1 -69 [19] or DP10 [18] is indeed the main heavy chain gene encoding RF from healthy human immunized donors, from peripheral blood lymphocytes (PBL) from RA patients and from paraproteins [27]. Some of the RF-encoding germline genes reported by other authors, mainly from studies of RF-secreting hybridomas [24,28,29], occurred recurrently in our investigation, namely the 3.23/DP-47/VH26, the 3.53/DP-42, the 4.59/DP-71/4.11 and the 4.18 germline gene.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, it has been confirmed that the corresponding germline gene 1 -69 [19] or DP10 [18] is indeed the main heavy chain gene encoding RF from healthy human immunized donors, from peripheral blood lymphocytes (PBL) from RA patients and from paraproteins [27]. Some of the RF-encoding germline genes reported by other authors, mainly from studies of RF-secreting hybridomas [24,28,29], occurred recurrently in our investigation, namely the 3.23/DP-47/VH26, the 3.53/DP-42, the 4.59/DP-71/4.11 and the 4.18 germline gene.…”
Section: Discussionmentioning
confidence: 93%
“…V λ genes have been shown to be critical parts of a number of human autoantibodies, including antibodies to double‐stranded DNA (29–32), antibodies to La/SSB and Ro/SSA (9, 33), RF (5, 34–37), and antibodies to lamin B (38) and phospholipids (39). Notably, however, these particular V λ gene segments have not previously been shown to encode autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on nucleotide sequence homology, the xlIIb L chains of the anti-rabbit IgG RF H4 (14) were most closely related to those of LBR150 and, thus, were also products of the germline hsigglll50 gene. Ermel et al (49) have recently reported that two other synovial cell-derived anti-rabbit IgG RF from another RF patient contained xlIIb L chains identical to those of RF H4 (14). The predominance of xlIIb L chains among RF with comparable specificity, especially those that are related to the hsiggl1150 VxlIIb germline gene, implies the functional importance of this gene in certain patients with RA and related diseases.…”
Section: Discussionmentioning
confidence: 99%